Activatable Second Near-Infrared Fluorescent Probes: A New Accurate Diagnosis Strategy for Diseases - Dong Li; Jie Pan; Shuyu Xu; Shiying Fu; Chengchao Chu; Gang Liu (Biosensors, 2021)
Recently, second near-infrared (NIR-II) fluorescent imaging has been widely applied in biomedical diagnosis, due to its high spatiotemporal resolution and deep tissue penetration. In contrast to the “always on” NIR-II fluorescent probes, the activatable NIR-II fluorescent probes have specific targeting to biological tissues, showing a higher imaging signal-to-background ratio and a lower detection limit. Therefore, it is of great significance to utilize disease-associated endogenous stimuli (such as pH values, enzyme existence, hypoxia condition and so on) to activate the NIR-II probes and achieve switchable fluorescent signals for specific deep bioimaging. This review introduces recent strategies and mechanisms for activatable NIR-II fluorescent probes and their applications in biosensing and bioimaging. Moreover, the potential challenges and perspectives of activatable NIR-II fluorescent probes are also discussed.